Epidermal growth factor receptor mRNA expression: A potential molecular escape mechanism from regorafenib. Issue 2 (27th January 2020) - Matsusaka, Satoshi; Hanna, Diana L.; Ning, Yan; Yang, Dongyun; Cao, Shu; Berger, Martin D.; Miyamoto, Yuji; Suenaga, Mitsukuni; Dan, Shingo; Mashima, Tetsuo; Seimiya, Hiroyuki; Zhang, Wu; et al.
Abstract: Regorafenib has improved the survival of patients with refractory metastatic colorectal cancer (mCRC), yet the mechanisms of inherited or acquired resistance are not well understood. A total of 50 patients with refractory mCRC were enrolled. Circulating tumor cell (CTC) enumeration was carried out at baseline, day 21 after initiation of regorafenib, and at the time of progression of disease (PD) using the CellSearch System (Veridex LLC, NJ, USA). Poly(A) mRNA was extracted from CTCs, and gene expression of epithelial and epithelial‐mesenchymal transition markers was analyzed by a multiplex‐PCR based DNA Chip. Patients with fewer than 3 CTCs at baseline and day 21 had a longer progression‐free survival than those with 3 or more CTCs (3.3 vs 2.0 months, P =  .008 and 3.3 vs 2.0 months, P =  .004, respectively). Patients with fewer than 3 CTCs at baseline and day 21 had a longer overall survival (OS) than those with 3 or more CTCs (10.0 vs 4.6 months, P <  .001 and 8.7 vs 3.8 months, P =  .003, respectively). In multivariable analysis, CTC counts remained significantly associated with OS at baseline and day 21 ( P  = .019 and P  = .028). Circulating tumor cell EGFR gene expression was upregulated at day 21 and/or PD in 64% of patients. Patients had significantly increased EGFR expression at PD compared to baseline ( P =  .041) and at day 21 and/or PD compared to baseline ( P =  .004). Our findings suggest that CTC count and EGFR expression could be useful markers of regorafenib efficacy and outcomes. Upregulation of CTC EGFR expression might be a molecular escape mechanism under regorafenib therapy. Abstract : We identified circulating tumor cell count as a prognostic marker in metastatic colorectal cancer patients treated with regorafenib. Circulating tumor cell EGFR expression was significantly increased with regorafenib at the time of disease progression, suggesting this to be a mode of resistance and lending further mechanistic evidence for the synergistic effects seen with regorafenib and anti‐ EGFR mAbs.